2008
DOI: 10.1093/cvr/cvn254
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of the prostaglandin E2 receptor EP4 improves cardiac function after myocardial ischaemia/reperfusion injury

Abstract: The data suggest that the EP4 agonist is effective for attenuation of I/R injury by suppressing MCP-1 and the infiltration of inflammatory cells, especially macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 36 publications
0
63
0
Order By: Relevance
“…EP4 agonist administration to mice subjected to myocardial infarction and ischemia/reperfusion induced a significant reduction in infarct size and preserved cardiac dysfunction. 8,12) Unilateral ureteral obstruction has been used to induce kidney fibrosis, and EP4 agonist mitigated interstitial fibrosis in this mouse model of chronic kidney disease. 21) These studies have indicated EP4 agonists have antifibrotic and organ protective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EP4 agonist administration to mice subjected to myocardial infarction and ischemia/reperfusion induced a significant reduction in infarct size and preserved cardiac dysfunction. 8,12) Unilateral ureteral obstruction has been used to induce kidney fibrosis, and EP4 agonist mitigated interstitial fibrosis in this mouse model of chronic kidney disease. 21) These studies have indicated EP4 agonists have antifibrotic and organ protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Infarct size of LV after ischemia-reperfusion injury was significantly larger in EP4 knockout mice, 8) and pharmacological activation of EP4 receptor ameliorated cardiac function in ischemia-reperfusion injury. 12) At the cellular level, intracellular cAMP, a downstream mediator of the EP4 receptor signaling, showed different responses to the EP4 agonist between cardiac fibroblasts and cardiac myocytes. 8) These findings suggest important roles for the EP4 receptor and its downstream signaling in cardioprotection.…”
Section: Editorial P3mentioning
confidence: 99%
“…The chest wall and the skin were then closed with a 3-0 silk suture. [12][13][14][15][16][17][18] This investigation conforms with the Guide for the Care and Use of Laboratory Animals of Tokyo Medical and Dental University. Animals used in this study were maintained in accordance with the Guide for the Care and Use of Laboratory Animals published by the US National Institute of Health (NIH Publication No.…”
Section: Methodsmentioning
confidence: 81%
“…M-mode views were used to measure the LV dimensions according to the American Society for Echocardiography leading edge method. [12][13][14][15][16][17][18] LV end-diastolic dimension (LVDd) and end-systolic dimension (LVDs), and fractional shortening (%FS= [(LVDd−LVDs) / LVDd]×100) were calculated from the M-mode recordings. Measurement of area at risk and infarct size: On day 1 after reperfusion, the anesthetized rats were intubated and thoracotomy was repeated.…”
Section: -18)mentioning
confidence: 99%
“…For example, increased levels of 14,15-epoxyeicosatrienoic acid (14, in murine myocardium produced by either overexpression of the cytochrome P450 enzyme CYP2J3 or by genetic knock-out of soluble epoxide hydrolase resulted in decreased mPTP opening probability, improved preservation of mitochondrial membrane potential (⌬ mt ), and attenuated damage after ischemia/reperfusion (17,20,21). The diverse effects of prostaglandin E 2 (PGE 2 ), a cyclooxygenase-2 product, on cardiac function have been documented, which include the reduction of cardiac ischemia/reperfusion injury and a contribution to myocardial hypertrophy via prostaglandin E 2 receptor signaling (22,23). In contrast, 12-HETE and 20-HETE induce increases in mitochondrial calcium concentration and myocardial infarct size during ischemia/reperfusion in mice (24 -26).…”
mentioning
confidence: 99%